Risk indicators for tooth loss in adult workers - Marília Jesus Batista; Lílian Berta Rihs; Maria da Luz Rosário de Sousa (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Tooth loss continues to be a prevalent condition in Brazilian adults and elderly individuals. The aim of this cross-sectional study, conducted among workers in a wholesale grocery chain in the State of São Paulo, was to identify risk indicators for tooth loss in adults. The presence of caries and periodontal status were examined in 387 adults aged 20-64 years, according to World Health Organization criteria. Two outcomes were analyzed: loss of one or more teeth, and loss of four or more teeth. Independent variables analyzed were demographic and socioeconomic factors, clinical conditions, use of dental services, and self-perceived oral health. Poisson regression models were used for multivariate statistical analysis. Participants were missing a mean of 5.38 teeth, and 76.9% (n = 297) had lost at least one tooth; the most frequently lost teeth were permanent molars. Older age and the presence of visible dental biofilm were associated significantly with the two tooth loss outcomes (p < 0.05). Individuals who had visited the dentist 3 or more years previously showed a lower prevalence of tooth loss (prevalence ratio = 0.79; 95% confidence interval, 0.68-0.91). Those with lower household incomes were significantly more likely to have lost four or more teeth (prevalence ratio = 1.35; 95% confidence interval, 1.07-1.70). Study results indicated that age and dental biofilm were risk indicators for tooth loss, independently of socioeconomic factors. These risk indicators should be considered when planning oral health programs for adults.